2011
DOI: 10.2478/v10197-011-0008-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Types of Recovery on Blood Lactate Removal After Maximum Exercise

Abstract: Introduction. Despite physiological changes caused by immersion in liquid medium, few studies have been conducted to determine the kinetics of blood lactate removal under these conditions. The aim of this study was to verify the effect of active recovery, using a specific water bike, on the blood lactate concentration after maximum intensity exercise. Material and method. Ten healthy cycling athletes performed an Anaerobic Threshold Test by Heart Rate (HR) on a bicycle ergometer and an Anaerobic Threshold Test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 17 publications
0
22
1
Order By: Relevance
“…The results of the present investigation clearly show that immersion to the shoulder in 29°C water does not improve lactate clearance in active or passive recovery. These results are not in agreement with the only two studies on this specific topic in literature, which showed an overall positive effect of the water environment in the clearance of blood lactate [ 9 , 10 ]. These conflicting results can probably be attributed to the substantial differences in the experimental design of the studies, in particular, the modalities of intensity control in active recovery and the identification of the starting point of the recovery phase.…”
Section: Discussioncontrasting
confidence: 90%
See 4 more Smart Citations
“…The results of the present investigation clearly show that immersion to the shoulder in 29°C water does not improve lactate clearance in active or passive recovery. These results are not in agreement with the only two studies on this specific topic in literature, which showed an overall positive effect of the water environment in the clearance of blood lactate [ 9 , 10 ]. These conflicting results can probably be attributed to the substantial differences in the experimental design of the studies, in particular, the modalities of intensity control in active recovery and the identification of the starting point of the recovery phase.…”
Section: Discussioncontrasting
confidence: 90%
“…[ 9 ], the subjects recovered actively in both land-based and water-based conditions at an intensity equal to 65% of the age-predicted HR (calculated with the 220-age formula), whereas in the study by Ferreira et al . [ 10 ], the subjects recovered actively in land-based and water-based conditions pedaling at 85% of the HR corresponding to the ventilatory threshold. Hence, both studies used HR to equalize the intensity levels of active recovery in the two different environmental conditions, even though it is known that during submaximal exercise, oxygen consumption being equal, HR in water is lower than it is on land by approximately 10–15 bpm [ 11 , 13 , 34 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations